La publicité comparative est – elle autorisée au Cameroun? - Marie-Solange TIENTCHEU HAKO (Juridical Tribune, 2014)
The Law No. 2006/018 of 29 December 2006 governing advertising in Cameroon has breached the lawfulness of comparative advertising. But the excessive caution of the legislature raises questions about the reality of this authorization, as the field of comparative advertising is limited. The total comparative advertising is considered as an act of unfair competition while the competitor comes out secure.